Présence des pauvres. La fouille de texte dans les sources de langue arabe du Maroc moderne (xviiie‑xixe siècles) - Antoine Perrier (Revue des Mondes Musulmans et de la Méditerranée)
This paper presents an experiment in text mining – i.e. keyword searching – on a corpus of sources from early modern Morocco: the administrative correspondence of a pasha of Fez (19th century), a biographical dictionary, a hagiography and a dynastic chronicle, three texts written between the 18th and 19th centuries. By investigating the presence of the poor in these texts extracted from manuscripts, this study highlights a common representation of poverty despite the geographical and thematic heterogeneity of these sources. The poor play an edifying role in accounts of the lives of saints, sultans and scholars, as a religious model and as a political representation of the people. As a first experiment in a wider project, text mining, despite its limitations, further illustrates the relevance of these sources for the social history of Morocco.